Adaptive PI Controller for Slip controlled Belt Continuously Variable Transmission. Issue 4 (2018) - Verbelen, Florian; Haemers, Michiel; Viaene, Jasper De; Derammelaere, Stijn; Stockman, Kurt; Sergeant, Peter
Abstract: The control of slip in a belt Continuously Variable Transmission (CVT) has been the subject of many research papers. Optimal control of the belt CVT is of major importance for the efficiency as demonstrated in literature. The challenge in optimizing that efficiency is in the reduction of the necessary clamping forces while the stability of the variable transmission is maintained. Although these problems have already been tackled to a certain extent, mostly fairly complex controllers are proposed. The goal of this paper is to propose a straightforward though effective method to control slip. The main idea of the paper is to use linearized equations of the slip dynamics to update the controller parameters in function of the operating point. This approach allows to reduce the highly nonlinear system to a first order transfer function which is easily controlled with a PI controller. Results based on extensive simulations show that the controller is robust against torque disturbances and speed ratio variations.